Case Report: Staged epicardial pacemaker implantation in a 740 g ELBW infant with 25 + 2 weeks of GA with congenital complete heart block - Tvildiani, Tamari; Riedl-Seifert, Teresa; Waitz, Markus; Dimpfl, Thomas; Paul, Thomas; Jenke, Andreas (Frontiers in Pediatrics, 2025)
BackgroundCongenital complete atrioventricular (AV) block is a rare but potentially fatal condition in neonates, especially those with extremely low birth weight (ELBW). Management in this population is challenging due to technical limitations and high comorbidity risk.Case presentationWe report the case of a female infant born at 25 + 2 weeks' gestation, weighing 740 g, with immune-mediated congenital complete AV block. Temporary epicardial pacing was initiated on day one due to persistent bradycardia and hemodynamic compromise. A dual-electrode strategy with alternating pacing sites maintained low thresholds for 90 days. A permanent pacemaker was implanted at 2,890 g. Despite complications including hydrops fetalis, intraventricular hemorrhage, hydrocephalus, and intestinal perforation, the patient was discharged in good condition.ConclusionThis case demonstrates the feasibility of staged pacemaker implantation in ELBW infants and supports individualized pacing strategies to optimize outcomes in this vulnerable population.